GABAA signaling, focal epileptiform synchronization and epileptogenesis - Avoli, Massimo; de Curtis, Marco; Lévesque, Maxime; Librizzi, Laura; Uva, Laura; Wang, Siyan (Frontiers in Neural Circuits, 2022)
Under physiological conditions, neuronal network synchronization leads to different oscillatory EEG patterns that are associated with specific behavioral and cognitive functions. Excessive synchronization can, however, lead to focal or generalized epileptiform activities. It is indeed well established that in both epileptic patients and animal models, focal epileptiform EEG patterns are characterized by interictal and ictal (seizure) discharges. Over the last three decades, employing in vitro and in vivo recording techniques, several experimental studies have firmly identified a paradoxical role of GABAA signaling in generating interictal discharges, and in initiating - and perhaps sustaining - focal seizures. Here, we will review these experiments and we will extend our appraisal to evidence suggesting that GABAA signaling does also contribute to epileptogenesis, i.e., the development of plastic changes in brain excitability that leads to the chronic epileptic condition. Overall, we anticipate that this information should provide the rationale for developing new specific pharmacological treatments for patients presenting with focal epileptic disorders such as mesial temporal lobe epilepsy.